THE MACRO-PRUDENTIAL POLICY AND BANK NON-PERFORMING ASSETS IN INDONESIA - Gustriani, Gustriani; Suhel, Suhel; Melliny, Vinny Dwi; Pertiwi, Rasyida; Nida, Rahma (Finance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2023)
This study examines the effect of the Macro-prudential Intermediation Ratio (MIR) as an instrument of Bank Indonesia's macro-prudential regulation on Non-Performing Assets (NPA) as one of the banking industry performance indicators in Indonesia. In addition, this study also examines several other independent variables such as bank assets as an indicator of bank size, Bank Indonesia interest rates (BI rate), and inflation as macroeconomic indicators and their effect on NPA. The NPA, MIR, and bank asset data used in this study consist of 109 commercial banks operating in Indonesia during the period from January 2015 to December 2020. This study uses an Ordinary Least Square (OLS) analysis approach by undertaking classical assumption tests and statistical tests. The results show that (1) MIR, bank assets, BI rate, and inflation simultaneously have a significant effect on NPA (2) Partially, bank assets have a negative and significant effect on NPA while other variables including macro-prudential policy have no significant effect on NPA (3) Variable MIR, bank assets, BI rate, and inflation can explain variations of NPA variable by 34% (4) Larger bank size encourages prudent financing and reduces NPA.